1991
DOI: 10.1007/bf01870405
|View full text |Cite
|
Sign up to set email alerts
|

Response of chloride efflux from skeletal muscle ofRana pipiens to changes of temperature and membrane potential and diethylpyrocarbonate treatment

Abstract: Efflux of 36Cl- from frog sartorius muscles equilibrated in two depolarizing solutions was measured. Cl- efflux consists of a component present at low pH and a pH-dependent component which increases as external pH increases. For temperatures between 0 and 20 degrees C, the measured activation energy is 7.5 kcal/mol for Cl- efflux at pH 5 and 12.6 kcal/mol for the pH-dependent Cl- efflux. The pH-dependent Cl-efflux can be described by the relation mu = 1/(1 + 10n(pK alpha-pH], where mu is the Cl- efflux increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…A protonation of the imidazole group of histidine associated with CI-channels could be the controlling reaction for pH-dependent CI-movements. These results are in agreement with the C1-fluxes measurements by Spalding et al (1991), who have found that DEPC affects the increment in CI-flux when the external pH is raised.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A protonation of the imidazole group of histidine associated with CI-channels could be the controlling reaction for pH-dependent CI-movements. These results are in agreement with the C1-fluxes measurements by Spalding et al (1991), who have found that DEPC affects the increment in CI-flux when the external pH is raised.…”
Section: Discussionsupporting
confidence: 83%
“…To minimize the loss of reagent by hydrolysis, the DEPC was added to solution immediately before the experiment. Since DEPC hydrolyzes spontaneously to ethanol and CO2 with a half-time of about 69 min at 20 ° C (Spalding et al 1991), the concentration of DEPC to which the fibres were exposed was somewhat less than the initial prepared concentration. As with the control fibres, currents in the treated fibres were measured in solution B at different pH values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high steady‐state chloride conductance, g Cl , of frog skeletal muscle fibre membranes, which is important for stabilization of the resting membrane potential, is strongly dependent on external pH. Cl − exchange under conditions of Cl − equilibrium in depolarized fibres (Skydsgaard, 1987) and g Cl in both normal (∼120 mM Cl − ) and high‐KCl Ringer solution (Hutter & Warner, 1967 a ) are all inactivated in acid medium with an apparent p K of ∼7 in Rana temporaria , possibly due to the protonation of histidines in the Cl − channels (Hutter & Warner, 1967 a,b ; Spalding, Taber, Swift & Horowicz, 1991). The acidification reduces g Cl more than it reduces the Cl − flux and there is evidence that a considerable fraction of the residual flux at low pH may be non‐conductive, possibly taking place via exchange diffusion (Harris, 1965; Hutter & Warner, 1967 b ; Skydsgaard, 1987).…”
mentioning
confidence: 99%